Diqqatu Tarjamat Nushush al-Akhbaar al-'Arabiyyat Ilaa al-Induuniisiyyat Bistikhdaami Bing Translator - Hasanah, Ummi; Zawawi, Moh (Jurusan Pendidikan Bahasa Arab IAIN Ponorogo, 2024)
Nowadays, sophisticated technology makes it easier for humans to do their work. Like Bing Translator, it is a translation machine that is popular with many people. Makes it easy for humans to translate documents into any language. However, we need to know that the accuracy of machine translation results and human translation results are very different. Therefore, the aims of this research are to analyze the results of accurate, less accurate and inaccurate translations of Arabic news texts on the Arabiya News site using Bing Translator. Data comes from 3 paragraphs of Arabic news text with the themes of health, politics and economics. This research is a qualitative descriptive research. Data collection techniques use reading and note-taking techniques. Meanwhile, the data analysis technique uses the Miles and Huberman model, namely data reduction, data display, and drawing conclusions. Based on 16 data obtained from 4 health news text data, 10 political news text data, and 4 economic news text data, it can be concluded that there are 5 accurate data, 9 less accurate data, and 4 inaccurate data. الملخص في الوقت الحاضر، تسهل التكنولوجيا المتطورة على البشر القيام بعملهم. مثل وجود Bing Translator، فهي آلة ترجمة تحظى بشعبية كبيرة لدى الكثير من الأشخاص. يجعل من السهل على البشر ترجمة المستندات إلى أي لغة. ومع ذلك، علينا أن نعرف أن دقة نتائج الترجمة الآلية ونتائج الترجمة البشرية مختلفان تمامًا. ولذلك فإن أهداف هذا البحث هي تحليل نتائج الترجمات الدقيقة وأقل دقة وغير الدقيقة للنصوص الإخبارية العربية على موقع العربية الإخبارية باستخدام Bing Translator. تأتي البيانات من 3 فقرات من النص الإخباري العربي مع موضوعات الصحة والسياسة والاقتصاد. هذا البحث هو بحث وصفي نوعي. تستخدم تقنيات جمع البيانات تقنيات القراءة وتدوين الملاحظات. وفي الوقت نفسه، تستخدم تقنية تحليل البيانات نموذج مايلز وهوبرمان، أي تقليل البيانات، وعرض البيانات، واستخلاص النتائج. بناءً على ستة عشر بيانات تم الحصول عليها من أربع بيانات نصية لأخبار صحية، وعشر بيانات نصية لأخبار سياسية، و أربع بيانات نصية لأخبار اقتصادية، يمكن استنتاج أن هناك خمس بيانات دقيقة، وتسع بيانات أقل دقة، وأربع بيانات غير دقيقة